Retargeting polymer-coated adenovirus to the FGF receptor allows productive infection and mediates efficacy in a peritoneal model of human ovarian cancer. - Green, N; Morrison, J; Hale, S; Briggs, S; Stevenson, M; Subr, V; Ulbrich, K; Chandler, L; Mautner, V; Seymour, L; Fisher, K (2008)
BACKGROUND: Transductional targeting of adenovirus following systemic or regional delivery remains one of the most difficult challenges for cancer gene medicine. The numerical excess and anatomical advantage of normal (non-cancer) cells in vivo demand far greater detargeting than is necessary for studies using single cell populations in vitro, and this must be coupled with efficient retargeting to cancer cells. METHODS: Adenovirus (Ad5) particles were coated with reactive poly[N-(2-hydroxypropyl)methacrylamide] copolymers, to achieve detargeting, and retargeting ligands were attached to the coating. Receptor-mediated infection was characterised in vitro and anticancer efficacy was studied in vivo. RESULTS: Polymer coating prevented the virus binding any cellular receptors and mediated complete detargeting in vitro and in vivo. These fully detargeted vectors were efficiently retargeted with the model ligand FGF2 to infect FGFR-positive cells. Specific transduction activity was the same as parental virus, and intracellular routing appeared unaffected. Levels of transduction were up to 100-fold greater than parental virus on CAR negative cells. This level of specificity permitted good efficacy in intraperitoneal cancer virotherapy, simultaneously decreasing peritoneal adhesions seen with parental virus. Following intravenous delivery FGF2 mediated unexpected binding to erythrocytes, improving circulation kinetics, but preventing the targeted virus from leaving the blood stream. CONCLUSIONS: Polymer cloaking enables complete adenovirus detargeting, providing a versatile platform for receptor-specific retargeting. This approach can efficiently retarget cancer virotherapy in vivo. Ligands should be selected carefully, as non-specific interactions with non-target cells (e.g. blood cells) can deplete the pool of therapeutic virus available for targeting disseminated disease.